Biodiversity Quadrupled—Revision of Easter Island and Salas y Gómez Bivalves - Raines, Bret; Huber, Markus (Zootaxa, 2012)
Seventy-one bivalve species, including fifteen new species living in the waters of Easter and Salas y Gómez Islands are hereindescribed: Nuculana (s.l.) anakena sp. nov., Lasaea eastera sp. nov., Borniola pasca sp. nov., Hyalokellia tahaia sp. nov., Tell-imya pauciradiata sp. nov., Tellimya tahaia sp. nov., Thecodonta rainesi sp. nov., Acrosterigma triangulare sp. nov., Herouvaliarapanui sp. nov., Moerella laperousea sp. nov., Abranda lamprelli sp. nov., Timoclea keegani sp. nov., Hyphantosoma crassumsp. nov., Hyphantosoma tenue sp. nov. and Austroneaera eastera sp. nov. Illustrated for the first time is the type material of Tin-daria salaria Dall, 1908. Results of this study also revise previously accepted levels of endemicity as well as species affiliation with other biogeographical areas.